Answer: 21 m
Step-by-step explanation:
Given
Mass of the first astronaut, m1 = 60 kg
Mass of the second astronaut, m2 = 80 kg
Distance moved by the first astronaut, d1 = 12 m
Distance moved by the second astronaut, d2 = ?
using the law of conservation of momentum, we can say
m1d1 = m2d2
So that, d2 = m1d1 / m2
d2 = (60 * 12) / 80
d2 = 720 / 80
d2 = 9 m
If we then take into account the distance of 12 m moved by the first astronaut. We have the total distance moved by the second astronaut to be 9 + 12 = 21 m
Thus, the distance moved by the heavier astronaut when the lighter astronaut has moved 12 m, is 21 m